AB0532 Profile of Henoch Schonlein Purpura (HSP) Nephritis: 23 Years Experience at A Tertiary Care Centre in North India. (15th July 2016) - Gupta, A.; Jindal, A.; Gupta, A.; Nada, R.; Minz, R.W.; Suri, D.; Rawat, A.; Singh, S.
Abstract : Background: HSP is one of the most common vasculitides of childhood. Glomerulonephritis is seen in approximately 30–50% of the patients and is the principal cause of morbidity and mortality in HSP patients. Objectives: We describe our experience of managing children with HSP Nephritis (HSPN). Methods: 314 children were registered in Pediatric Rheumatology Clinic, Advanced Pediatrics Centre, PGIMER, Chandigarh with a diagnosis of HSP based on EULAR/PRINTO/PRES criteria during the period from January 1993 to June 2015. A retrospective case review of all patients with HSPN with respect to clinical features, pathological findings and treatment was done. HSPN was defined based on urine erythrocyte >5/HPF and/or proteinuria >150mg/24 hr. Patients were divided into four clinical types according to the laboratory results: (1) isolated hematuria (urine erythrocyte >5/HPF and proteinuria <150 mg/24hr); (2) minimal proteinuria (150 mg/24hr ≤ proteinuria <25 mg/kg); (3) moderate proteinuria (25 mg/kg ≤ proteinuria <50 mg/kg); (4) massive proteinuria (≥50 mg/kg). The severity of the renal pathological findings was determined based on the classification of the International Study of Kidney Disease (ISKDC), from grades I – VI (1) . Results: Renal involvement was seen in 64 patients (20.4%) after a mean duration of 32.3 days from the onset of symptoms of HSP. Renal manifestations developed in 57.8% of the patients within 4 weeks of symptom onset, in 84.4% within 8 weeks and in 100% within 6 months. Massive proteinuria was the most common clinical feature seen in 56.7% of the patients followed by minimal proteinuria in 21.7%, moderate proteinuria in 15% and isolated hematuria in 6.7% of cases. Hypertension was seen in 24 patients. 4 patients had deranged renal function tests.13 patients developed a clinical relapse of the renal disease after a mean interval of 551.5 days from the remission of first episode. Albuminuria with microscopic hematuria was the most common presentation of second episode (77%) followed by isolated albuminuria (23%). Kidney biopsy was done in 48 patients. Three fourth of the patients had histological grade II or IIIa. 75% of patients with grade ≥ IV had gross hematuria at presentation. 25 patients received prednisolone alone, 31 received azathioprine in addition to prednisolone, while cyclophosphamide and mycophenolate mofetil were used in 5 and 1 patient respectively. Patients were followed up for a mean period of 3.6 years during which 13 were lost to follow up, 1 expired while 3 patients each are currently on prednisolone and azathioprine. Nephritis resolved in 48 patients (75%) with mean duration of renal involvement being more in patients with nephritis at presentation (429 days) as compared to patients who develop nephritis in follow up (321 days). Conclusions: In our cohort of HSPN, 100% of the patients developed renal involvement within 6 months of the onset of symptoms of HSP with massive proteinuria being the most common clinical feature. Grade II and IIIa were the most common renal pathological grades seen in 75% of the patients. References: Appel GB, Radhakrish J, D'Agati VD (2004) Secondary glomerular disease. In: Brenner BM (ed) The kidney, 7th edn. Saunders, Philadelphia, pp 1381–1482 Disclosure of Interest: None declared